Assessment of factors influencing the quality of surface and ground water in the Hout Bay river catchment - Pearce, Meryl Winsome (Rhodes University, Faculty of Science, Department of Geography, 1989)
An investigation into the quality of surface water and ground water was conducted during 1988 in the 38,8 kmÂ² Hout Bay River catchment near Cape Town. The main objective of the study was to determine those areas and activities which constitute a pollution source and to ascertain the relative proportion which each contributes to the pollution problem and health risk of the surf zone of the beach at Hout Ba . The objective was achieved by monitoring the chemical and microbiological attributes of the Hout Bay River, its tributaries and stormdrains in wet and dry conditions on a routine basis and during storm events. Hout Bay is a rapidly developing residential area in which sewage disposal occurs by means of septic tank soakaway systems. Ground water quality was monitored to investigate the contribution to contamination by septic tank effluent. Results showed that stormdrain effluent in dry and wet conditions and surface runoff during rainfall were the main vectors of pollution. Although the pollution concentration was high during dry conditions the greatest pollution discharge to the surf zone of Hout Bay occurred during storm events. In view of the proposed residential development it is imperative that pollution control measures be undertaken so as to secure the future recreational and aesthetic value of Hout Bay
Keywords: Water -- South Africa -- Hout Bay; Hydrology Water -- Pollution -- South Africa -- Hout Bay; Water quality -- South Africa -- Hout Bay; Aquatic ecology; Water quality; Hout Bay river (South Africa); Groundwater -- South Africa -- Hout Bay